THE ALPHA-VINYLATION OF BETA-DICARBONYL COMPOUNDS BY ALK-1-ENYL-LEAD TRIACETATES - Moloney, M; Pinhey, J (1988)
Treatment of (E,E)-distyrylmercury (1) with lead tetra-acetate gave a mixture of (E)-styrylmercury acetate (3) and (E)-styryl-lead triacetate (2), which decomposed to (E)-styryl acetate (4) and lead(II) acetate. The vinyl-lead compound (2), generated in this way, reacted rapidly with β-keto ester (5) to give the α-(E)-styryl derivative (6) in synthetically useful yield. This procedure for the α-vinylation of (5) has been applied to the divinylmercury compounds (7)-(13), and to the synthesis of the α-(E)-styryl β-dicarbonyl compounds (28), (30), (32), and (34). Compounds (6), (28), (30), (32), and (34). Compounds (6), (28), (30), (32), and (34) have also been produced by reaction with lead compound (2) generated by reaction of tributyl-(E)-styrylstannane (36) and lead tetra-acetate. Isolation of the relatively stable cyclopent-1-enyl-lead triacetate (21b), and its reaction with keto ester (5) to give a quantitative yield of compound (18), provided evidence that vinyl-lead triacetates are the vinylating species.